101 = 100 + 1
102 = 100 + 2
103 = 100 + 3
and so on, and
99 = 100 - 1
98 = 100 - 2
97 = 100 - 3
and so on. Then the
-th term of the sum, where
, is
![(-1)^(n-1)(100+n)(100-n)=(-1)^n(n^2-100)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/3mficfa1euvb6b9ps5ual8h05qrvxw21sg.png)
We want to compute the sum,
![(101\cdot99)-(102\cdot98)+\cdots+(149\cdot51)-(150\cdot50)=\displaystyle\sum_(n=1)^(50)(-1)^n(n^2-100)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/23c0p0dthtthrh9yngc3gjr4u7d85wmh8p.png)
We have
![\displaystyle\sum_(n=1)^(50)(-1)^n(n^2-100)=\sum_(n=1)^(50)(-1)^nn^2-100\sum_(n=1)^(50)(-1)^n](https://img.qammunity.org/2020/formulas/mathematics/middle-school/oue4kx7pf013gycpk7ijgejoodqpwq4xw8.png)
but notice that in the last sum, we're just adding the same number of 1s and -1s together, so its value is 0 and
![\displaystyle\sum_(n=1)^(50)(-1)^n(n^2-100)=\boxed{\sum_(n=1)^(50)(-1)^nn^2}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/6r4svwe55hk5x9zbi2uy8n6hts4py2bfiy.png)
In case you're not familiar with the formula for the sum of consecutive squares, we can derive it here. Recall that
![\displaystyle\sum_(n=1)^k1=k](https://img.qammunity.org/2020/formulas/mathematics/middle-school/iwwkg6fsuv0z4g4b2zpng6men9w44sj14m.png)
![\displaystyle\sum_(n=1)^kn=\frac{k(k+1)}2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/36o4g5h19l9oh4tibimpiy6j2xap8nj9oc.png)
Notice that
![(n+1)^3-n^3=(n^3+3n^2+3n+1)-n^3=3n^2+3n+1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/hazixpokl7ppgkrbw33r0ad5po27axf6kr.png)
and that
![\displaystyle\sum_(n=1)^k((n+1)^3-n^3)=(2^3-1^3)+(3^2-2^3)+\cdots+(k^3-(k-1)^3)+((k+1)^3-k^3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/x4kjb55cexwy0fzu58qhw21fdg8riq27h1.png)
![\implies\displaystyle\sum_(n=1)^k((n+1)^3-n^3)=(k+1)^3-1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/whw9po13mhggs0nnbkmtor6quoio8tyemx.png)
Then
![(k+1)^3-1=\displaystyle\sum_(n=1)^k(3n^2+3n+1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/4ozsk1msg0o7ujxbeb2n4xbjjpunxfbkly.png)
![\displaystyle\sum_(n=1)^k3n^2=(k+1)^3-1-3\frac{k(k+1)}2-k](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ehw3les2937ajy4907md925uy860rlvcap.png)
![\displaystyle\sum_(n=1)^kn^2={k(k+1)(2k+1)}6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/i5pqi7f67a72jx0msxws9fyrl3sijxshmk.png)
Now consider the cases where
is either odd or even.
- If
is odd, we can write
, where
. Then
![\displaystyle\sum_(m=1)^(25)(-1)^(2m-1)(2m-1)^2=-\sum_(m=1)^(25)(4m^2-4m+1)=-\frac{2\cdot25\cdot26\cdot51}3+2\cdot25\cdot26-25](https://img.qammunity.org/2020/formulas/mathematics/middle-school/v0pvmo08dx1qlexyamu106eud6wgnp3c1a.png)
![\displaystyle\sum_(m=1)^(25)(-1)^(2m-1)(2m-1)^2=-20,825](https://img.qammunity.org/2020/formulas/mathematics/middle-school/v5ciuq1bdzu70oozcopmxg3cf5js9qnu6k.png)
- If
is even, we can write
and so
![\displaystyle\sum_(m=1)^(25)(-1)^(2m)(2m)^2=\sum_(m=1)^(25)4m^2=\frac{2\cdot25\cdot26\cdot51}3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/1q5hm4op0i01iryr9t06pn81qlj0lth9ve.png)
![\displaystyle\sum_(m=1)^(25)(-1)^(2m)(2m)^2=22,100](https://img.qammunity.org/2020/formulas/mathematics/middle-school/f7m8yh3mqrwtjgb33qoch5w8zkojlcd114.png)
The original sum is obtained by adding the odd- and even-indexed sums together:
![\displaystyle\sum_(n=1)^(50)(-1)^nn^2=-20,825+22,100=\boxed{1275}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8yfdraer3f9q7mofcwnxpr9ev2e0otaro0.png)